1,4-Dimethylpiperazine-2,3-dione - Themmila Khamrang; C. Ponraj; Madhukar Hemamalini; G. Jerald Maria Antony; Dhandayutham Saravanan (IUCrData, 2024)
In the title compound, C6H10N2O2, the piperazine-2,3-dione ring adopts a half-chair conformation. In the crystal, the molecules are linked by weak C—H...O hydrogen bonds, forming (010) sheets.